MXene quantum dot tip heterojunction material with high photothermal conversion efficiency and preparation method thereof

By laying Ti3C2MXene quantum dots on the surface of Co3O4 nanoneedles, forming a tip heterojunction structure, the problem of rapid recombination of photogenerated electron-hole pairs of MXene quantum dots is solved, and the photothermal conversion efficiency is significantly improved. It is suitable for low-light intensity conditions and continuous Application of thermal effects.

CN119465144AActive Publication Date: 2025-02-18NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411537420.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Although the narrow bandgap properties of MXene quantum dots enhance light absorption capacity, they are also prone to trigger rapid recombination of photogenerated electron-hole pairs, shorten their lifetimes, and reduce the photo-heat conversion efficiency, especially under low light intensity conditions or require continuous thermal effects. in application scenarios.

Method used

By laying Ti3C2MXene quantum dots on the surface of Co3O4 nanoneedles, a tip heterojunction structure is formed, and the MXene quantum dots are fixed using heterogeneous charge interaction forces to build an efficient electron-hole separation interface to reduce the recombination of photogenerated carriers.

Benefits of technology

It significantly improves the photothermal conversion efficiency, enhances the light absorption capacity and thermal energy conversion performance of the material, especially in low light intensity conditions or in application scenarios where continuous thermal effects are required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465144A_ABST
    Figure CN119465144A_ABST
Patent Text Reader

Abstract

The invention discloses an MXene quantum dot tip heterojunction material with high photothermal conversion efficiency. The MXene quantum dot tip heterojunction material comprises a substrate and a Co3O4 nanoneedle array structure grown on the substrate in situ, ti3C2MXene quantum dots are loaded on the surface of the Co3O4 nanoneedle, and the Ti3C2MXene quantum dots are fixed on the surface of the Co3O4 nanoneedle through the interaction force of heterogeneous charges. The invention also discloses a preparation method of the MXene quantum dot tip heterojunction material. The preparation method comprises the following steps: (1) preparing a Co3O4 nanoneedle structure arranged in an array on a substrate by using a hydrothermal method; and (2) under the irradiation of an ultraviolet lamp, putting the product in the step (1) into an MXene quantum dot solution, and soaking for 6-8 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency, and also relates to a method for preparing the material. Background Art

[0002] Photothermal conversion technology is the conversion of absorbed light energy into thermal energy, and plays an important role in the fields of solar energy utilization, photothermal therapy and thermal catalysis. In the field of photothermal conversion, two-dimensional transition metal carbides, nitrides or carbonitrides MXene have attracted much attention due to their unique photothermal conversion properties. Due to their efficient light absorption ability, MXene nanosheets can absorb light energy in a wide spectral range (including ultraviolet to near-infrared) and efficiently convert it into thermal energy. Its two-dimensional structure enables photons to be reflected multiple times within the nanosheets, improving the light absorption efficiency. Compared with MXene nanosheets, MXene quantum dots (MDQs) can further improve the photothermal conversion performance of the material. Although the narrow bandgap characteristics of MXene quantum dots enhance the light absorption ability, they are also prone to induce rapid recombination of photogenerated electron-hole pairs, thereby shortening their lifespan, reducing the photothermal conversion efficiency, and making it difficult for the material to maintain a high temperature state, especially under low light intensity conditions or when a continuous thermal effect is required. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a MXene quantum dot tip heterojunction material with high photothermal conversion efficiency, in which Co3O4 nanoneedles and Ti3C2MXene quantum dots form a tip heterojunction structure, and an efficient electron-hole separation interface can be formed at the contact interface between the two, thereby effectively reducing the recombination of photogenerated carriers and improving the photothermal conversion efficiency; another purpose of the present invention is to provide a method for preparing the above-mentioned Ti3C2MXene quantum dot tip heterojunction material.

[0004] Technical solution: The MXene quantum dot tip heterojunction material with high photothermal conversion efficiency described in the present invention includes a substrate and a Co3O4 nanoneedle array structure grown in situ on the substrate; Ti3C2MXene quantum dots are laid on the surface of the Co3O4 nanoneedles, and the Ti3C2MXene quantum dots are fixed on the surface of the Co3O4 nanoneedles through the interaction force of heterogeneous charges, and the two form a tip heterojunction structure.

[0005] The material of the present invention has an array-type tip heterojunction structure. On the one hand, the tip structure of the material can significantly enhance the local light field and concentrate light energy through the "hot spot" effect, thereby improving the light absorption efficiency; on the other hand, the array-type tip heterojunction structure can cause the incident light to undergo multiple local reflections and scatterings in these areas, thereby increasing the residence time and absorption depth of the light; in addition, the tip morphology can also induce a local plasma resonance effect, further improving the interaction efficiency between photons and materials, and significantly improving the photothermal conversion performance of the material.

[0006] Wherein, the substrate is one of foamed nickel, foamed copper, carbon cloth or carbon paper; the tip carrier Co3O4 nanoneedle is in-situ grown on the substrate.

[0007] Among them, the mass of Ti3C2MXene quantum dots loaded on the tip carrier Co3O4 nanoneedles is 1 to 10 mg.

[0008] The preparation method of the above material comprises the following steps:

[0009] (1) A Co3O4 nanoneedle structure arranged in an array is prepared on a substrate using a hydrothermal method;

[0010] (2) Under the irradiation of ultraviolet light with a wavelength of 360 nm, the product of step (1) is placed in a Ti3C2MXene quantum dot solution and immersed for 6 to 8 hours to obtain a Ti3C2MXene quantum dot tip heterojunction material with MXene quantum dots loaded on Co3O4 nanoneedles.

[0011] Wherein, in step (1), the temperature of the hydrothermal reaction is 100-120° C., and the hydrothermal time is 6-12 h.

[0012] Among them, a Co3O4 nanoneedle structure arranged in an array is prepared on a nickel foam substrate with a thickness of 1 mm. The specific process is: 0.1-0.2g Co(NO3)2·6H2O, 0.3-0.5g NH4F and 2-3g urea are dissolved in 20-30mL deionized water, and a reaction solution is obtained after stirring; the nickel foam is placed in 3M HCl to remove surface oxides, and then rinsed with deionized water three times and placed in the reaction solution, and hydrothermally heated at 100-120°C for 10-20h; after the hydrothermal reaction is completed, the initial product Co(OH)F is obtained; the initial product is first rinsed with deionized water, then blown dry with nitrogen, and finally calcined in air at 400-500°C for 3-4h to obtain a Co3O4 nanoneedle structure grown in situ on the substrate and arranged in an array.

[0013] Wherein, in step (2), the preparation process of MXene quantum dot solution is: 1-1.2g Ti3AlC2, 12-15mL9M HCl and 1.6-2g LiF are mixed and etched at 40°C for 24-30h; after etching, a few-layer MXene solution is prepared by multiple centrifugal washing and ultrasonic crushing; the pH of the MXene solution is adjusted to 9-10 with ammonia water, and then hydrothermal at 100-120°C for 10-12h; after the hydrothermal is completed, the supernatant is taken and filtered through a filter membrane with a pore size of 0.2μm to obtain a Ti3C2MXene quantum dot solution. Under the irradiation of ultraviolet light with a wavelength of 360nm, the product of step (1) is placed in the Ti3C2MXene quantum dot solution and soaked for 6-8h.

[0014] Among them, the average particle size of Ti3C2 MXene quantum dots is 1 to 2 nm.

[0015] In step (2), the irradiation intensity of the ultraviolet lamp is 5 to 6 W m -2 .

[0016] Wherein, in step (2), in the Ti3C2MXene quantum dot tip heterojunction material, the mass of the Ti3C2MXene quantum dots loaded on the tip carrier Co3O4 nanoneedles is 1 to 10 mg.

[0017] The present invention uses Co3O4 nanoneedles as the base semiconductor, and after being evenly mixed with negatively charged MXene quantum dots, a cutting-edge heterojunction is formed under ultraviolet light irradiation, thereby significantly improving the photothermal conversion performance. Combining Ti3C2MXene quantum dots with Co3O4 nanoneedles to form a cutting-edge heterojunction material helps to build an efficient electron-hole separation interface, reduce the recombination of photogenerated carriers, and improve the photothermal conversion efficiency. The heterojunction of Ti3C2MXene quantum dots and Co3O4 nanoneedles also exhibits high infrared emissivity and effectively dissipates heat through infrared radiation. Therefore, in addition to its outstanding performance in photothermal applications, the cutting-edge heterojunction structure of the present invention also has important potential in the field of infrared false targets. Its efficient photothermal conversion and rapid response capabilities can quickly generate strong infrared radiation, simulate the infrared characteristics of real targets, and effectively protect real targets.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The material of the present invention tightly couples Ti3C2MXene quantum dots with two-dimensional Co3O4 nanoneedles, which can construct an efficient electron-hole separation interface, thereby reducing the recombination of photogenerated carriers and thus improving the photothermal conversion efficiency; (2) The Ti3C2MXene quantum dot tip heterojunction material of the present invention can be used for the thermal conductivity of the Ti3C2MXene quantum dots under the influence of infrared lamps (200mW cm -2) Within 5 minutes of irradiation, the surface temperature quickly reaches 93.9°C, which greatly improves the light-to-heat conversion performance of MXene quantum dots. (3) The Ti3C2MXene quantum dot tip heterojunction material of the present invention has a full-band infrared emissivity of not less than 0.85 at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The transmission electron microscope image and particle size distribution diagram of the MXene quantum dots in Example 1;

[0020] Figure 2 This is a scanning electron microscope image of the heterojunction of the Co3O4 nanoneedle and MXene tip in Example 1;

[0021] Figure 3 This is a physical picture of the MXene quantum dot tip heterojunction material in Example 1;

[0022] Figure 4 This is a transmission electron microscopy image of the tip heterojunction of Co3O4 nanoneedles and MXene quantum dots in Example 1;

[0023] Figure 5 This is the photothermal response diagram of the MXene quantum dot tip heterojunction in Example 1;

[0024] Figure 6 is the infrared emissivity of the MXene quantum dot tip heterojunction in Example 1. DETAILED DESCRIPTION

[0025] Example 1

[0026] The method for preparing a MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency of the present invention comprises the following steps:

[0027] (1) 0.1 g of Co(NO3)2·6H2O, 0.3 g of NH4F and 2 g of urea were dissolved in 20 mL of deionized water, stirred for 30 min to obtain a reaction solution, and the reaction solution was transferred to a 50 mL reactor; a nickel foam treated with 3 M HCl (the purpose of the treatment was to remove oxides on the surface of the nickel foam) was placed in the reaction solution and hydrothermally heated at 120° C. for 10 h; after the hydrothermal reaction was completed, the nickel foam was taken out, rinsed with deionized water for 5 to 10 times, and dried with nitrogen to obtain the initial product Co(OH)F on the nickel foam; finally, the nickel foam was calcined in air at 400 to 500° C. for 3 to 4 h to obtain a Co3O4 nanoneedle structure in situ grown on the nickel foam substrate and arranged in an array;

[0028] (2) Weigh 1 g of Ti3AlC2 raw material and place it in a 50 mL reactor, add 12 mL of 9 M HCl and 1.6 g of LiF, and etch at 40 ° C for 30 h; after etching, centrifuge and wash several times at 3500 rpm until the pH of the supernatant is neutral; after the last washing and centrifugation, ultrasonicate the aqueous solution in a N2 atmosphere for 3 h; after the ultrasonication, adjust the pH of the solution to 9-10 with ammonia water, and hydrothermally heat at 120 ° C for 12 h; after the hydrothermal reaction, take the supernatant and filter it through a 0.2 μm pore size filter membrane to obtain a MXene quantum dot solution;

[0029] (3) The Co3O4 nanoneedles prepared in step (1) were irradiated with a 360 nm ultraviolet lamp (the irradiation intensity of the ultraviolet lamp was 5 W m -2 ) is placed in the MXene quantum dot solution (concentration of 0.2×10 -3 wt%) and immersed in it for 8h to obtain a MXene quantum dot tip heterojunction material, which was recorded as MXeneQDs1@Co3O4; in the material, the mass of MXene quantum dots loaded on the Co3O4 nanoneedles was 1mg.

[0030] Example 2

[0031] The method for preparing a MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency of the present invention comprises the following steps:

[0032] (1) 0.2 g of Co(NO3)2·6H2O, 0.5 g of NH4F and 3 g of urea were dissolved in 30 mL of deionized water, stirred for 30 min to obtain a reaction solution, and the reaction solution was transferred to a 50 mL reactor; the nickel foam from which the surface oxide was removed by 3 M HCl was placed in the reaction solution, and hydrothermal treatment was performed at 120° C. for 10 h; after the hydrothermal reaction was completed, the nickel foam was taken out, rinsed with deionized water for 5 to 10 times, and dried with nitrogen to obtain the initial product Co(OH)F; finally, the nickel foam was calcined in air at 400 to 500° C. for 3 to 4 h to obtain a Co3O4 nanoneedle structure in situ grown on the nickel foam substrate and arranged in an array;

[0033] (2) Weigh 1 g of Ti3AlC2 raw material and place it in a 50 mL reactor, add 12 mL of 9 M HCl and 1.6 g of LiF, and etch at 40 ° C for 30 h; after etching, centrifuge and wash several times at 3500 rpm until the pH of the supernatant is neutral; after the last washing and centrifugation, ultrasonicate the aqueous solution in a N2 atmosphere for 3 h; after the ultrasonication, adjust the pH of the solution to 9-10 with ammonia water, and hydrothermally heat at 120 ° C for 10 h; after the hydrothermal reaction, take the supernatant and filter it through a 0.2 μm pore size filter membrane to obtain a MXene quantum dot solution;

[0034] (3) The Co3O4 nanoneedles prepared in step (1) were irradiated with a 360 nm ultraviolet lamp (the irradiation intensity of the ultraviolet lamp was 5 W m -2 ) is placed in the MXene quantum dot solution (concentration of 1×10 -3 wt%) and immersed in it for 8h to obtain a MXene quantum dot tip heterojunction material, which was recorded as MXeneQDs2@Co3O4; in the material, the mass of MXene quantum dots loaded on the Co3O4 nanoneedles was 5mg.

[0035] Example 3

[0036] The method for preparing a MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency of the present invention comprises:

[0037] (1) 0.2 g of Co(NO3)2·6H2O, 0.5 g of NH4F and 3 g of urea were dissolved in 30 mL of deionized water, stirred for 30 min to obtain a reaction solution, and the reaction solution was transferred to a 50 mL reactor; the nickel foam from which the surface oxide was removed by 3 M HCl was placed in the reaction solution, and hydrothermal treatment was performed at 120° C. for 10 h; after the hydrothermal reaction was completed, the nickel foam was taken out, rinsed with deionized water for 5 to 10 times, and dried with nitrogen to obtain the initial product Co(OH)F; finally, the initial product was calcined in air at 400 to 500° C. for 3 to 4 h to obtain a Co3O4 nanoneedle structure in situ grown on the nickel foam substrate and arranged in an array;

[0038] (2) Weigh 1 g of Ti3AlC2 raw material and place it in a 50 mL reactor, add 12 mL of 9 M HCl and 1.6 g of LiF, and etch at 40 ° C for 30 h; after etching, centrifuge and wash several times at 3500 rpm until the pH of the supernatant is neutral; after the last washing and centrifugation, ultrasonicate the aqueous solution in a N2 atmosphere for 3 h; after the ultrasonication, adjust the pH of the solution to 9-10 with ammonia water, and hydrothermally heat at 120 ° C for 10 h; after the hydrothermal reaction, take the supernatant and filter it through a 0.2 μm pore size filter membrane to obtain a MXene quantum dot solution;

[0039] (3) The Co3O4 nanoneedles prepared in step (1) were irradiated with an ultraviolet lamp having a wavelength of 360 nm and an irradiation intensity of 5 W m -2 Place the MXene quantum dot solution (concentration of 2×10 -3 wt%) and immersed in it for 8h to obtain a MXene quantum dot tip heterojunction material, which was recorded as MXeneQDs3@Co3O4; in the material, the mass of MXene quantum dots loaded on the Co3O4 nanoneedles was 10mg.

[0040] Figure 1 This is a transmission electron microscope image of the MXene quantum dots obtained in step (2) of Example 1; Figure 1 a It can be seen that MXene quantum dots are evenly distributed; Figure 1 From the particle size distribution diagram (b), the size of MXene quantum dots is mainly 1.5 nm.

[0041] Figure 2 The scanning electron microscope images of the Co3O4 nanoneedle prepared in step (1) of Example 1 and the MXene quantum dot tip heterojunction formed in step (3); Figure 2 a It can be seen that the Co3O4 nanoneedles are evenly distributed; Figure 2 b It can be seen that the surface of Co3O4 nanoneedles is slightly rough after loading MXene quantum dots.

[0042] Figure 3 This is a physical picture of the MXene quantum dot tip heterojunction material in Example 1, and the material is black.

[0043] Figure 4 The transmission electron micrographs of the Co3O4 nanoneedle prepared in step (1) of Example 1 and the MXene quantum dot tip heterojunction formed in step (3) show that the nanoneedle morphology is well maintained and the MXene quantum dots are evenly distributed on the nanoneedle.

[0044] Figure 5 This is the photothermal response diagram of the MXene quantum dot tip heterojunction material prepared in Example 1. Figure 5 As can be seen in a, under infrared light (200mW cm -2 ), the surface temperature of the MXene quantum dot tip heterojunction material quickly (5min) reached 93.9°C, while the surface temperatures of the MXene quantum dots prepared in step (2) (in this comparison process, the mass of the MXene quantum dots is the same as the effective mass of the MXene quantum dots in the MXene quantum dot tip heterojunction material) and the Co3O4 nanoneedles prepared in step (1) were 71.6°C and 65.7°C, respectively. Figure 5 As can be seen in b, under the irradiation of xenon lamp (1kW cm -2 ), the surface temperature of the heterojunction material at the tip of the MXene quantum dots quickly reached 65.2°C, while the surface temperatures of the MXene quantum dots and Co3O4 nanoneedles were 53.1°C and 50.3°C.

[0045] Figure 6 The infrared emissivity of the MXene quantum dot tip heterojunction materials prepared in Example 1, Example 2 and Example 3. It can be seen from the figure that the full-band infrared emissivity of the MXene quantum dot tip heterojunction material of the present invention at room temperature is not less than 0.85.

Claims

1. A MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency, characterized in that: It includes a substrate and a Co3O4 nanoneedle array structure grown in situ on the substrate; the surface of the Co3O4 nanoneedle is loaded with Ti3C2MXene quantum dots, and the Ti3C2MXene quantum dots are fixed on the surface of the Co3O4 nanoneedle through the interaction force of heterogeneous charges.

2. The MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency according to claim 1, characterized in that: The substrate is one of foamed nickel, foamed copper, carbon cloth or carbon paper.

3. The MXene quantum dot tip heterojunction material with high light-to-heat conversion efficiency according to claim 1, characterized in that: The mass of Ti3C2MXene quantum dots loaded on Co3O4 nanoneedles is 1 to 10 mg.

4. The method for preparing the MXene quantum dot tip heterojunction material according to claim 1, characterized in that: The steps include: (1) Co3O4 nanoneedle structures arranged in an array are prepared on a nickel foam substrate using a hydrothermal method; (2) Under ultraviolet light, the product of step (1) is immersed in a Ti3C2MXene quantum dot solution to obtain a Ti3C2MXene quantum dot tip heterojunction material in which Ti3C2MXene quantum dots are loaded on Co3O4 nanoneedles.

5. The preparation method according to claim 4, characterized in that: In step (1), the temperature of the hydrothermal reaction is 100 to 120° C., and the hydrothermal time is 6 to 12 hours.

6. The preparation method according to claim 5, characterized in that: A Co3O4 nanoneedle structure arranged in an array is prepared on a nickel foam substrate. The specific process is as follows: 0.1-0.2g Co(NO3)2·6H2O, 0.3-0.5g NH4F and 2-3g urea are dissolved in 20-30mL deionized water, and a reaction solution is obtained after stirring; the substrate is placed in the reaction solution and hydrothermally heated at 100-120°C for 10-20h; after the hydrothermal reaction is completed, a primary product Co(OH)F is obtained; the primary product is first rinsed with deionized water, then blown dry with nitrogen, and finally calcined in air at 400-500°C for 3-4h to obtain a Co3O4 nanoneedle structure grown in situ on the substrate and arranged in an array.

7. The preparation method according to claim 4, characterized in that: In step (2), the preparation process of the MXene quantum dot solution is as follows: 1-1.2 g Ti3AlC2, 12-15 mL 9M HCl and 1.6-2 g LiF are mixed and etched at 40°C for 24-30 h; after etching, a few layers of MXene solution are prepared by multiple centrifugal washing and ultrasonic crushing; the pH of the MXene solution is adjusted to 9-10 with ammonia water, and then hydrothermal treatment is performed at 100-120°C for 10-12 h; after the hydrothermal treatment is completed, the supernatant is taken and filtered through a filter membrane with a pore size of 0.2 μm to obtain a Ti3C2MXene quantum dot solution.

8. The preparation method according to claim 7, characterized in that: The average particle size of Ti3C2MXene quantum dots is 1 to 2 nm.

9. The preparation method according to claim 4, characterized in that: In step (2), the irradiation intensity of the ultraviolet lamp is 5 to 6 W m -2 。 10. The preparation method according to claim 4, characterized in that: In step (2), the soaking time is 6 to 8 hours.

Citation Information

Patent Citations

  • Preparation of super-wettability cobalt oxide nano-needle porous membrane and application of super-wettability cobalt oxide nano-needle porous membrane to emulsion separation

    CN105617871A

  • Device for detecting lead ions

    CN108287186A

  • Preparation method and applications of hairy ball type Ti3C2(MXene)nanometer material

    CN110723737A

  • Preparation method of 0D / 2D quantum dot / graphene nano roll heterostructure electrode material

    CN112103485A

  • Carbon nitride quantum dot / (001) surface exposed titanium dioxide / titanium carbide MXene as well as preparation method and application thereof

    CN115318329A

Cited By

  • Preparation method of efficient water evaporation MXene-CuS pyramid array photo-thermal structure

    CN120681823A